IMPLICATIONS OF INTERFAITH MARRIAGE DIVORCE ON CHILDREN’S CARE RIGHTS IN INDONESIA - Putu Ayu Diah Laksmi Dewi; I Nyoman Sujana; Putu Ayu Sriasih Wesna (Journal of International Legal Communication, 2022)
This research is a normative legal research, which concerns the implications of the Divorce Divorce Marriage of Different Religious Against Child Custody. Problem 1). What is the legal protection for interfaith marriages in Indonesia ? 2). What are the implications of the divorce of interfaith marriages for child custody? The purpose of this study was to determine the implications of divorce between different religions for child custody. The benefit of this research is to provide input for the government to take a policy and provide knowledge to the public about interfaith marriages. Results of the discussion: 1). Based on article 35 of the Population Administration Act of interfaith marriages can be recorded based on the determination of the Court as long as it does not violate legal norms and norms of decency, because the Marriage Act does not mention that interfaith marriages are prohibited. 2). If no agreement is found, the court will decide who has the right to obtain custody of the child. Conclusions: 1). Interfaith marriages can be recorded if based on the determination of the court in accordance with the provisions of the Law on State Administration article 35 letter a. 2). Child custody of a minor falls to the care of his mother, as long as the mother has never been proven guilty in court. While a child who is capable of law can choose between his father or mother as the holder of the right to care.